Relevance of Education Curriculum with Local Culture: Perspective of Islamic Education Management according To Ki Hajar Dewantara and Paulo Freire - Nursikin , Mukh; Utami, Mita (JIEMAN: Journal of Islamic Educational Management, 2024)
This article discusses the relevance of educational curriculum management to the integration of local culture of the community, with the approach of an Islamic education management perspective inspired by the thoughts of two great educational figures, Ki Hajar Dewantara and Paulo Freire. The purpose of this study is to analyze the educational curriculum in the perspective of Ki Hajar Dewantara and Paulo Freire and its relevance to the management of educational curriculum based on local culture in the context of Islamic education. The method used in this research is descriptive qualitative with the type of literature study, which involves analyzing literature such as books, journals, magazines, and other sources. The results show that Ki Hajar Dewantara's thought implies three main centers of education, namely family, school, and community, which are interrelated in shaping the character and independence of students. He emphasized the importance of understanding, living and applying local culture in the learning process, which is in line with the principles of Islamic education that prioritizes the relevance of education to the social and cultural context. Meanwhile, Paulo Freire, with his concept of critical education, emphasizes the importance of dialogical and empowerment processes, where learners are invited to understand their social and cultural realities as a basis for change